Winter soil respiration in a humid temperate forest: The roles of moisture, temperature, and snowpack. Issue 12 (23rd December 2016) - Contosta, Alexandra R.; Burakowski, Elizabeth A.; Varner, Ruth K.; Frey, Serita D.
Abstract: Winter soil respiration at midlatitudes can comprise a substantial portion of annual ecosystem carbon loss. However, winter soil carbon dynamics in these areas, which are often characterized by shallow snow cover, are poorly understood due to infrequent sampling at the soil surface. Our objectives were to continuously measure winter CO2 flux from soils and the overlying snowpack while also monitoring drivers of winter soil respiration in a humid temperate forest. We show that the relative roles of soil temperature and moisture in driving winter CO2 flux differed within a single soil‐to‐snow profile. Surface soil temperatures had a strong, positive influence on CO2 flux from the snowpack, while soil moisture exerted a negative control on soil CO2 flux within the soil profile. Rapid fluctuations in snow depth throughout the winter likely created the dynamic soil temperature and moisture conditions that drove divergent patterns in soil respiration at different depths. Such dynamic conditions differ from many previous studies of winter soil microclimate and respiration, where soil temperature and moisture are relatively stable until snowmelt. The differential response of soil respiration to temperature and moisture across depths was also a unique finding as previous work has not simultaneously quantified CO2 flux from soils and the snowpack. The complex interplay we observed among snow depth, soil temperature, soil moisture, and CO2 flux suggests that winter soil respiration in areas with shallow seasonal snow cover is more variable than previously understood and may fluctuate considerably in the future given winter climate change. Key Points: Variable controls on CO2 flux within a single soil‐to‐snow profile Soil moisture had a negative control on CO2 flux from soil; soil temperature had a positive control on CO2 flux from the snowpack Changes in soil moisture and temperature were driven by shifts in air temperature and snow depth